Stretchable Conductive Composites Based on Metal Wools for Use as Electrical Vias in Soft Devices. (21st January 2015) - Lessing, Joshua; Morin, Stephen A.; Keplinger, Christoph; Tayi, Alok S.; Whitesides, George M.
Abstract : Soft devices can be bent, stretched, and compressed reversibly, but conventional wires are rigid. This work describes stretchable composites that are easily fabricated with simple tools and commodity materials, and that can provide a strategy for electrical wiring that meets certain needs of soft devices. These composites are made by combining metal wool and elastomeric polymers. Embedding fine (average fiber width ≈25 μm) steel wool (or other metal wools) in a silicone polymer creates an electrically conductive path through the nonconductive elastomer. This composite is flexible, stretchable, compressible, inexpensive, and simple to incorporate into the bodies of soft devices. It is also electrically anisotropic, and shows maximum conductivity along the majority axis of the fibers, but maximum extension perpendicular to this axis. The utility of this composite for creating an electrically conductive path through an elastomer was demonstrated in several devices, including: a soft, solderless breadboard, a soft touch sensor, and a soft strain gauge. Abstract : Soft devices can be bent, stretched, and compressed reversibly, but conventional wires are rigid. This work describes stretchable composites that are easily fabricated with simple tools and commodity materials, and that can provide a strategy for electrical wiring that meets certain needs of soft devices. The utility of this composite is demonstrated in several devices, including a soft, solderless breadboard.